Strategies for Building Reference Standards for Autoantibodies - Sheldon, Joanna; Dellavance, Alessandra (Frontiers in Immunology, 2015)
Producing robust, certified, traceable reference material for autoantibody testing is a vital element in maintaining the validity of results that are generated in the daily clinical laboratory routine. This is a huge challenge because of the high number of variables involved in the detection and measurement of the autoantibodies. The production of such materials is time consuming and needs rigorous attention to detail; this is best achieved by an overarching independent body who will oversee the process in a “not for profit” manner. Much effort has been made to build international standards for quantitative and qualitative assays based on monoclonal antibodies, obtained from affinity purification and plasmapheresis. The big challenge is to respect individual differences in immune response to the same antigen. A promising ongoing initiative is the construction of pools with monospecific samples from different individuals.